2011
DOI: 10.1007/s00412-011-0335-8
|View full text |Cite
|
Sign up to set email alerts
|

Pairing of lacO tandem repeats in Arabidopsis thaliana nuclei requires the presence of hypermethylated, large arrays at two chromosomal positions, but does not depend on H3-lysine-9-dimethylation

Abstract: Fluorescent chromatin tagging by the lacO operator/lac repressor system in Arabidopsis thaliana is useful to trace distinct chromatin domains in living cells. Nevertheless, the tandem repeats of the tagging system may alter the spatial organisation of chromatin within nuclei by increasing homologous pairing as well as association with heterochromatin. Efficient homologous pairing occurs if lacO repeat arrays of ∼10 kb are present at two loci, either on the same chromosome or on different chromosomes. DNA hypom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…These results are consistent with the focused analysis of 13 A. thaliana genomic regions by 4C (Grob et al 2013). Experiments with lacO repeat arrays integrated in the A. thaliana genome have suggested that the clustering of lacO sequences at distant loci depended on heterochromatic marks (Jovtchev et al 2011). The clustering of heterochromatin is in line with the observation of ''AB compartments'' from animal Hi-C data sets, where euchromatin and heterochromatin are spatially segregated (Lieberman-Aiden et al 2009).…”
Section: Discussionsupporting
confidence: 76%
“…These results are consistent with the focused analysis of 13 A. thaliana genomic regions by 4C (Grob et al 2013). Experiments with lacO repeat arrays integrated in the A. thaliana genome have suggested that the clustering of lacO sequences at distant loci depended on heterochromatic marks (Jovtchev et al 2011). The clustering of heterochromatin is in line with the observation of ''AB compartments'' from animal Hi-C data sets, where euchromatin and heterochromatin are spatially segregated (Lieberman-Aiden et al 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Homologous transgenic tandem repetitive sequences pair more often with each other and associate with chromocenters in A. thaliana nuclei than flanking euchromatin (Jovtchev et al 2008(Jovtchev et al , 2011Pecinka et al 2005). Similarly, sister chromatid cohesion at endogenous centromeric repetitive sequences is increased compared with euchromatic sequences in Arabidopsis.…”
Section: Discussionmentioning
confidence: 87%
“…Successful application of the LacO/LacI system for GFP tagging of distinct chromosomal loci in living A. thaliana has already been described (Kato and Lam, 2001;Pecinka et al, 2005;Watanabe et al, 2005;Jovtchev et al, 2008Jovtchev et al, , 2011. Indeed, preliminary data suggest that the LacO/LacI system can be exploited also for ectopic plant kinetochore assembly, providing dicentric chromosomes for subsequent splitting into artificial minichromosomes (Teo et al, 2013).…”
Section: De Novo Generation Of Centromeres At Tandem Repeatsmentioning
confidence: 99%